To green or not to green: The influence of green marketing on consumer behaviour in the hotel industry - Mercade-Mele, Pere; Molina-Gómez, Jesús; Garay, Lluís (MDPI, 2019)
Different studies have analysed how green marketing influences the sustainable image of tourist companies or have focused on the identification and engagement between these companies and their consumers. In any case, the question of how this process influences consumers’ behaviour in the hotel industry requires even more in-depth study, with the intention of explaining the changes that occur in the current consumer and how this affects the hotel industry. This study is useful to demonstrate that beyond the direct influence of green marketing on green word of mouth indicators there are other indirect influences which are represented by other mediating variables: green attitudinal loyalty and green trust. From the literature on green marketing and the conceptual approaches offered by the Hierarchy of Effects Model and the Associate Learning Principles, this study conducted an empirical approach using a structured questionnaire. The questionnaire responses, obtained from a sample of 238 hotel users, were analysed using a Structural Equation Modelling (SEM) to test the research hypothesis related to the positive influence of green marketing on green trust, green attitudinal loyalty, and green word of mouth. This research provides theoretical and managerial implications to help executives adopt green marketing strategies, thanks to their positive effects on consumers’ recommendations, both direct and indirect, through loyalty and trust. It is concluded that green marketing actions have a greater effect on their indirect relationship with word of mouth than on their direct relationship and that loyalty is the aspect with the highest influence regarding trust.
Keywords: Turismo - Aspectos ambientales; sustainability; green marketing; green trust; green attitudinal loyalty; green word of mouth; hospitality; hierarchy of effects; associative learning principles